The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1016/j.tics.2003.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Understanding bilingual memory: models and data

Abstract: Bilingual memory research in the past decade and, particularly, in the past five years, has developed a range of sophisticated experimental, neuropsychological and computational techniques that have allowed researchers to begin to answer some of the major long-standing questions of the field. We explore bilingual memory along the lines of the conceptual division of language knowledge and organization, on the one hand, and the mechanisms that operate on that knowledge and organization, on the other. Various int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
1
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(104 citation statements)
references
References 61 publications
(64 reference statements)
5
90
1
4
Order By: Relevance
“…Conceptually, this finding indicates that L2 speakers process lexical -conceptual information of words in sentences in a manner similar to L1 speakers. This extends the increasingly accepted idea of a shared lexical storage system for words in L1 and L2 (for a review, see French and Jacquet, 2004) to a shared lexical access/retrieval system for both systems. Hernandez and colleagues further predict on the basis of a computational model proposed by Li et al (2004) that overlap of L1 and L2 semantic representations will be greatest for late learners of L2 (Hernandez et al, 2005).…”
Section: L2 Speakerssupporting
confidence: 64%
See 1 more Smart Citation
“…Conceptually, this finding indicates that L2 speakers process lexical -conceptual information of words in sentences in a manner similar to L1 speakers. This extends the increasingly accepted idea of a shared lexical storage system for words in L1 and L2 (for a review, see French and Jacquet, 2004) to a shared lexical access/retrieval system for both systems. Hernandez and colleagues further predict on the basis of a computational model proposed by Li et al (2004) that overlap of L1 and L2 semantic representations will be greatest for late learners of L2 (Hernandez et al, 2005).…”
Section: L2 Speakerssupporting
confidence: 64%
“…In other words, while the processing of semantic information might be quite similar between L1 and L2, processing of syntactic structure may be quite different. In fact, precisely, this distinction between semantic and syntactic processing has been suggested (for review of evidence for shared lexical storage system, see French and Jacquet, 2004). If semantic information in L1 and L2 is supported by the same cortical network, but syntactic information is not, this will clearly cause studies conducted at the word level (Klein, 2003;Chee et al, 1999bChee et al, , 2000Chee et al, , 2003 to show greater similarities between L1 and L2 than studies conducted at the sentence or discourse level (Dehaene et al, 1997;Perani et al, 1996Perani et al, , 1998Wartenburger et al, 2003).…”
Section: Introductionmentioning
confidence: 93%
“…In Kroll and Stewart's (1994) revised hierarchical model, beginning L2 learners' access conceptual representations in their nondominant language by initially translating to L1. However, conceptual mediation in L2 is feasible for highly proficient learners but reliance on L2-L1 lexical links to access conceptual meaning remain nonetheless (French & Jacquet, 2004). Kroll and Stewart (1994) demonstrated that even highly fluent bilinguals possess asymmetrical strength between L1-L2 lexical and conceptual links, where conceptual links are stronger for L1 than for L2 and L2-L1 lexical links are stronger than L1-L2 links.…”
mentioning
confidence: 99%
“…These models are used to explain how words and their meanings are represented in bilingual lexicosemantic organisation. They can therefore be categorized as models of bilingual representations (for a recent review of models of bilingual memory and their development, see Francis, 1999;French & Jacquet, 2004;Kroll & Tokowicz, 2005).…”
Section: Models Of Bilingual Memorymentioning
confidence: 99%
“…In recent years much progress can be observed in the development of models of bilingual memory resulting in the emergence of computational and connectionist models (see French & Jacquet, 2004, for a review). Still there are many issues that should be identified and explained in a theoretical framework (for a review of methodological and conceptual issues see Grosjean, 2004).…”
Section: Is There a Need For A New Bilingual Model?mentioning
confidence: 99%